Occupational gender stereotypes and problem-solving in Italian adolescents. Issue 3 (27th May 2017) - Ginevra, Maria Cristina; Nota, Laura
ABSTRACT: The first purpose of the study was to establish how Italian adolescents perceive jobs in the newly emerging economy sectors as well as more traditional jobs from gender-stereotyped and gender-segregated perspectives. The second purpose was to verify the role of problem-solving and gender in gender-role stereotyping. A total of 217 Italian high school students were involved. A questionnaire developed by Miller and Hayward was used to examine the students' occupational gender-role stereotyping, segregation and interests. The Problem-Solving Inventory was administered to examine problem-solving. Adolescents perceived most jobs as being gender-stereotyped and -segregated. Female gender and problem-solving ability were associated with a reduced tendency to perceive jobs as gender-stereotyped.